Applying nitrogen fertilizer increased anthocyanin in vegetative shoots but not in grain of purple rice genotypes - Supaporn Yamuangmorn (2018)
© 2018 Society of Chemical Industry BACKGROUND: Anthocyanin is a major antioxidant compound in purple rice, with properties that can protect against oxidative damage in some human diseases. This study was undertaken to determine if nitrogen (N) fertilizer can enhance anthocyanin and antioxidant levels in four purple Thai rice genotypes. RESULTS: The anthocyanin concentration and antioxidant capacity were increased in the shoots of N120 plants compared with plants without N. The leaves had higher anthocyanin concentration and antioxidant capacity than the stem+leaf sheath. Maximum shoot anthocyanin concentrations occurred at tillering and then declined by 87–94% at maturity. Antioxidant capacity was high at tillering and panicle initiation and declined by 26% in leaves and by 98% in the stem+leaf sheath at maturity. Unlike in the vegetative shoot, grain anthocyanin was not affected by the addition of N fertilizer. The response of grain antioxidant capacity to N fertilizer was affected by genotype, increasing in KPY by 45% but decreasing in K19959 by 30% in N120 plants. CONCLUSION: Applying N fertilizer could be a promising way to improve the antioxidative properties in vegetative parts for use in rice-grass juice, cosmetics and other products, especially the young leaves, which contained high values of anthocyanin as well as antioxidant capacity. However, further field studies should be undertaken to optimize N utilization for anthocyanin and antioxidant capacity in purple rice genotypes. © 2018 Society of Chemical Industry.